พฤติกรรมของคาน-เสาคอนกรีตเสริมเหล็กจากการรับแรงกระแทกด้านข้าง - เจนวิทย์ ศรีจันทร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research investigated the behavior of reinforced concrete beam-columns under impact load at mid-span and L/4. A 300 kg falling weight was dropped 6 times repeatedly at low height of 0.35, 0.35, 0.70, 0.70, 0.70 and 0.70 m. The experiment comprised sixteen reinforced concrete beamcolumns with 0.22x0.22 m. square section and a clear span length of 3.00 m After the impact test, sixteen experiment repeated static testing and four experiment static testing. The designed variables were (1) the magnitude of the axial load of 0.00 , 0.14, 0.21 and 0.28 of Axial load (2) the spacing of stirrup RB6@100 and RB6@200 and (3) location of impact load . From the test, it was found that, the impact load repetition deteriorated the beams impact resistance especially for the non-axial load specimens. At low small impact load, cracks were propagated and strains in reinforcements were increased. However, at the higher impact load and more number of the repetition, local damage at the impact location was observed. The increase in cracking and strains of the reinforcements were found locally at the impact location. The higher magnitude of axial load effectively reduced the deterioration and minimized the local damage at the impact point. And the test static result, it was found that, the beam-columns that pass static test only will not have crack at near support. However specimens that passed the impact test will have crack at near support due to impact load ,causing vibrate and damage on specimens. The axial load prevented the local damage and shear plug failure mechanism. The higher axial load and stirrup increase the propagation of the previous flexural cracks. For the effect of stirrup spacing the diagonal crack formed at the impact location was more serve for the largely spaced stirrup specimens. The higher axial load and stirrup reduces tensile stress leading to a small number of crack, regardless of the stirrup spacing. In addition, it prevents the local damage at the impact point and shear plug failure mechanism.